The Status of Outsourcing Services in a Specialized Tehran Hospital Using SWOT - Parisa Mehdizadeh; Nooredin Dopeykar; Ezzatollah Gol-Alizadeh; Maryam Yaghoubi (Baqiyatallah University of Medical Sciences, 2016)
Background: Outsourcing in healthcare is a cost-effective strategy that reduces costs and increases service quality. Managers must attempt to outsource healthcare services using scientific methods. Objective: This study is a strategic analysis of the outsourcing of health services in one specialty and subspecialty hospital in Tehran. Methods: This mixed method study (quantitative-qualitative) was performed in 2014 at one of the biggest specialty hospitals in Tehran. Data was collected through interviews, focus discussion groups (FDG), and the internal and external factors evaluation matrix. The study population comprised managers and directors of the hospital. Data was analyzed using Excel 2010 software and SWOT analysis. Results: The final scores for internal and external factors were 2.16 and 2.68, respectively, indicating the hospital had a conservative strategic position for choosing outsourcing strategies. Conclusion: Since this hospital had a conservative strategic position in outsourcing, managers were able to change their outsourcing strategy while considering its advantages and disadvantages and determining the type of services to be outsourced.